Pelaksanaan Metode Bin Nazhar di Pondok Pesantren an- Nur Padangsidimpuan - Dame Siregar, Nur Rahma Primaulina Pulungan & Muhammad Arsad Nasution & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The background of the problem in this study is that students at the Islamic boarding school (Islamic boarding school) an-Nur, memorize al-Qur'an specifically for all students, both Tsanawiyah and Aliyah. The success achieved by these students has met the target, where students must hafidz 1 juz in every one semester. The formulation of the problem in this study is how the implementation of the bin Nazhar tahfidzul quran method in Islamic boarding schools and how is the success rate. The aim is to find out the implementation of al-Qur'an learning in an-Nur Islamic boarding school and to know the level of success. This research is a field research that uses data collection techniques, namely observation, interviews, and documentation, but also takes several related books such as the Practical Complete Guide to Tajwid Tahfidzh Tahsin for Beginners by Raisya Maula Ibnu Rusyd and Quick Ways to Memorize the Qur'an. by H. Sa'dulloh, SQ The results of this study indicate that the implementation of the bin Nazhar method in the Tahfidz program is to make targets for Tsanawiyah starting from juz 30 and Aliyah starting from juz. So the average students memorized a minimum of 12 juz while they were in the pesantren and some were more. The success rate achieved is approximately 80%, where another 20% of them perfect their reading that is not yet perfect in pronunciation.